20 years of economic reforms in Sub-Saharan Africa : how farmers from the "Office du Niger" irrigation system in Mali reacted ? - (:unkn) unknown (My University, 2000)
Achieving an Asian style Green Revolution remains an elusive goal for most of Sub-Saharan Africa. The Malian "Office du Niger," while more productive than irrigated rice schemes elsewhere in Africa, exhibited higher costs and lower yields than Asian systems for many years. A prolonged period of agricultural stagnation led the Malian government to implement economic and institutional reforms in the 1980s. These reforms were followed by changes in the structure and functions of the "Office du Niger" itself, by additional policy reforms, and finally by the devaluation of the CFA Franc in 1994. After 20 years of reform, producers are now realizing increased incomes due to productivity gains. Factors contributing to this evolution include: (1) investments to upgrade irrigation systems, (2) extension messages focusing on new varieties and transplanting seedlings, and (3) liberalisation, devaluation and import policy reforms.
Keywords: African Research